Publication Mapping regarding E-Government Implementation using VosViewer and Biblioshiny - Putri Kinanti, Novrianti; Yuadi, Imam (Journal of Economics, Business, and Government Challenges, 2023)
This study aims to analyze the development of research regarding the implementation of e-Government in 2019-2023 and can be used as a literature review for further research on how to implement e-Government. The method used in this study is a bibliometric analysis conducted in the Scopus global literature journal by including the keyword "E-Government Implementation". The results of the bibliometric analysis show that This study aims to analyze the development of research regarding the implementation of e-Government in 2019-2023. The method used in this study is a bibliometric analysis conducted in the Scopus global literature journal by including the keyword "E-Government Implementation". The results of the bibliometric analysis show that 2019 was the year with the most publications regarding e-government, reaching 209 publications, with the most research subjects in the fields of social and computer science, and the country that published the most research was Indonesia. E-government keywords are the most used keywords in several studies related to the implementation of e-Government.